Evaluation of the Early Results of Percutaneous Ethanol Ablation in Patients with Primary Hyperparathyroidism - Yankova I.; Shinkov A.; Kovatcheva R. (Acta Medica Bulgarica, 2022)
Percutaneous ethanol ablation (PEA) is an alternative non-surgical method for the treatment of patients with primary hyperparathyroidism (PHPT), suitable in cases with comorbidities and high surgical risk.